Autonomous learning in the third semester students of the roreign language teaching program at a state university in Sincelejo, Sucre (2019)
This research seeks to explore the impact of the use of metacognitive strategies in autonomous training during the process of learning English as a second language directed to a group of students of the foreign language program at a public university. In the same way, this research aims to examine the slam of training on the implementation of metacognitive strategies in the academic achievements of second semester students in an English class. It tends to be qualitative research and uses the format of an action case study to allow an analysis and perception of the participants through their voices and for an intervention with a small but diverse sample. The data will be collected through focus groups, interviews and artifact instruments that will provide information that will be collected and analyzed using a learner-based Approach as an essential and vital practice and the general inductive foreign language field. According to Machemer and Crawford (2007), learner-based approach is not a passive experience, but active learning which helps learners to learn by themselves. This provides the students with the most important tools to learn in an independent way in which the teacher does not stop participating in the process. The expected results will try to provide information on how students use metacognitive strategies and the use of self-assessment in their learning process, taking into account autonomous learning as a tool to help them reach their academic achievements. This research can also serve as a point of focus for student teachers because they will be able to develop and implement learning strategies